Letter : Anglo-Spanish Clearing Agreement - Pethick-Lawrence, Frederick William Pethick-Lawrence, Baron, 1871-1961
012a-0003-001 FROM THE RT. HON. F. W. PETHICK-LAWRENCE, MP. 11 Old Square Lincoln's Inn, W.C.2. 15th. December, 1938. Dear Mr. Tewson, re Anglo-Spanish Clearing Agreement. Mr. Pethick-Lawrence asks me to thank you for your letter of yesterday, and to say that he has to-day written direct to Mr. Fernandez Shaw. Yours faithfully, Secretary. The Assistant Secretary, T.U.C., Transport House, Smith Square 292/946/12a/3